2021
DOI: 10.1097/md.0000000000023950
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of acupuncture for the recovery of gastrointestinal function of patients with gastric cancer in the postoperative period

Abstract: Background: Gastric cancer (GC) is the most common malignant tumors in the world and surgical resection remains the primary treatment for it. Postoperative patients often suffer from gastrointestinal dysfunction as the most common side effects of surgery for GC patients. Acupuncture has a regulatory effect on gastrointestinal function. We conducted this study to assess the effectiveness of acupuncture on the restoration of gastrointestinal function of postoperative patients with GC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…T lymphocytes have an effector function by secreting various cytokines or activating other immune cells that play a role in tumor immunity, and Zhu Yanhua et al showed that the serum immune indexes CD3+, CD4+, CD4+/CD8+ levels were increased and CD8+ levels were decreased by acupuncture at the acupuncture points of "Foot San Li and Qi Hai" [8] . The increase of CD4+ T lymphocyte ratio is an important marker of postoperative immune reconstitution, which can inhibit leukocyte aggregation, promote local circulation, affect the establishment of collateral circulation, reduce the vascular permeability of the body, and inhibit tumor recurrence in patients after surgery [9] . Liu Yu and Tan Jing et al moxibustion has elevated CD4+ and CD3+ levels, moxibustion has certain inhibitory effects on tumor growth and metastasis, and blood vessels in the tumor are significantly reduced [10][11] .…”
Section: Acupuncture Regulates Immune Cellsmentioning
confidence: 99%
“…T lymphocytes have an effector function by secreting various cytokines or activating other immune cells that play a role in tumor immunity, and Zhu Yanhua et al showed that the serum immune indexes CD3+, CD4+, CD4+/CD8+ levels were increased and CD8+ levels were decreased by acupuncture at the acupuncture points of "Foot San Li and Qi Hai" [8] . The increase of CD4+ T lymphocyte ratio is an important marker of postoperative immune reconstitution, which can inhibit leukocyte aggregation, promote local circulation, affect the establishment of collateral circulation, reduce the vascular permeability of the body, and inhibit tumor recurrence in patients after surgery [9] . Liu Yu and Tan Jing et al moxibustion has elevated CD4+ and CD3+ levels, moxibustion has certain inhibitory effects on tumor growth and metastasis, and blood vessels in the tumor are significantly reduced [10][11] .…”
Section: Acupuncture Regulates Immune Cellsmentioning
confidence: 99%
“…The restoration of postoperative gastrointestinal function, a topic extensively discussed in studies such as Saad et al 1 and a recent meta-analysis by Li et al 2 consistently highlights the favorable effects of early feeding in facilitating the recovery of puerperal women. These findings collectively highlight the protective role of early feeding in the postoperative period and its alignment with both national and international guidelines advocating for abbreviated fasting approaches.…”
mentioning
confidence: 99%
“…Cesarean section introduces a substantial volume of blood and amniotic fluid into the peritoneal cavity, requiring abdominal cavity cleaning, which can trigger intestinal disorders, 2 and consequently pain, abdominal distension, and difficulties in initiating adequate breastfeeding. 3 Previous research has demonstrated that early feeding post-cesarean section, by mitigating nausea and vomiting and promoting more frequent bowel movements, plays a vital role in the recovery of patients.…”
mentioning
confidence: 99%